Morphological Study of the Persian Leopard (Panthera pardus saxicolor) Tongue. (24th January 2017) - Sadeghinezhad, J.; Sheibani, M. T.; Memarian, I.; Chiocchetti, R.
Summary: This study described the morphological features of the Persian leopard ( Panthera pardus saxicolor ) tongue using light and scanning electron microscopy techniques. The keratinized filiform papillae were distributed all over the entire dorsal surface of the tongue and contained small processes. They were changed into a cylindrical shape in the body and conical shape in the root. The fungiform papillae were found on the apex and margin of the tongue. Few taste pores were observed on the dorsal surface of each papilla. The foliate papillae on the margins of the tongue were composed of several laminae and epithelial fissures. Taste buds were not seen within the non‐keratinized epithelium. The vallate papillae were six in total and arranged in a "V" shape just rostral to the root. Each papilla was surrounded by a groove and pad. Taste buds were seen within their lateral walls. Lyssa was visible on the ventral surface of the tongue tip and was found as cartilaginous tissue surrounded by thin connective tissue fibres. The core of the tongue was composed of lingual glands, skeletal muscle and connective tissue. These glands were confined to the posterior portion of the tongue and were composed of many serous cells and a few mucous cells. The results of this study contributed to the knowledge of the morphological characteristics of the tongue of wild mammals and provided data for the comparison with other mammals.